Pengaruh Dana Pihak Ketiga (DPK) dan Non Performing Loan (NPL) Terhadap Return On Assets (ROA) Melalui Pertumbuhan Kredit (Studi Kasus Pada BUSN Devisa Yang Terdaftar di BEI Periode 2011-2015) - Khairunnisa Arifin; Ike Purnamasari (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Khairunnisa Arifin. 2016. The Effect of Third Party Fund (DPK) and Non Performing Loan (NPL) in Return on Assets (ROA) Through Credit Growth at National Private Banks (BUSN) Foreign Exchange listed in Indonesia Stock Exchange (BEI). Mentored by Prof.Dr.H.Djoko Setyadi, M.Sc  and Mrs. Ike Purnamasari, SE., MM. The purpose of this research is to examine and analyze the effect of Third Party Fund (DPK) and Non Performing Loan (NPL) to Return on Assets (ROA) trough Credit Growth. The dependent variable in this research is the Return on Assets (ROA). The independent variables in this research is a Third Party Fund (DPK) and Non Performing Loan (NPL), and Credit Growth as Intervening Variablel. The population in this research is 22 National Private Banks (BUSN) Foreign exchange listed in the Indonesia Stock Exchange (BEI) in 2011-2015. The sampling technique used purposive sampling method and obtained a sample of 8 banks. Methods of data analysis used  Path Analysis. The results in this research showed that Third Party Fund (DPK) positive significant effect on credit growth. Non Performing Loan (NPL) negative significant effect on the growth of Credit. Third Party Fund (DPK) negative significant effect on Return on Assets (ROA). Non Performing Loan (NPL)  negative significant effect on Return on Assets (ROA). The credit growth has negative significant effect on Return on Assets (ROA). As  intervening variable Credit Growth not  able to mediate the relationship between  the Third Party Funds (DPK) and Return on Assets (ROA). Credit Growth as intervening variable able to mediate the relationship between the Non Performing Loan (NPL) and Return on Assets (ROA). Keywords: Third Party Fund (DPK), Non Performing Loan (NPL), Return on  Assets (ROA), Credit Growth.